RETRACTED: How does multidimensional R&D investment affect green innovation? Evidence from China - Shi, Yang; Yang, Can (Frontiers in Psychology, 2022)
Under the background of green development, multi-dimensional R&D investment and institutional quality have injected strong power into green innovation. Based on China's provincial panel data from 2009 to 2018, this paper examines the threshold effect of R&D and R&D personnel input on China's green innovation capability from three perspectives: political institutional quality, economic institutional quality and legal institutional quality. The core research results show that the influence of R&D on China's green innovation capability has obvious double-threshold effect based on institutional quality. This paper expands the research on the influencing factors of green innovation and the influence effect of multi-dimensional R&D investment, and provides a theoretical basis for regional green innovation management. In addition, the research results of this paper provide a reference for accurately formulating regional green innovation capability promotion strategy.